2016
DOI: 10.1021/acsmedchemlett.6b00338
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Peptoid with Antifungal Activity against Cryptococcus neoformans

Abstract: Studies show there is an increasing rate of fungal infections, especially in immunocompromised patients and treatments for fungal genera, such as Aspergillus, Candida, and Cryptococcus, carry significant cytotoxicity with an increasing prevalence of antifungal resistance. We have previously reported a high-throughput assay for identifying peptoids with antimicrobial properties from combinatorial libraries. Here we report the application of this assay in identifying a peptoid with antifungal properties against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…This small structural difference increases in vivo stability by inhibiting protease recognition . A host of studies have identified antibacterial peptoids, as summarized in a recent review by Molchanova et al ., however, there are limited reports of antifungal peptoids . Using a high‐throughput screening assay, we have recently identified a tripeptoid with antifungal properties against C. neoformans from a combinatorial peptoid library .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This small structural difference increases in vivo stability by inhibiting protease recognition . A host of studies have identified antibacterial peptoids, as summarized in a recent review by Molchanova et al ., however, there are limited reports of antifungal peptoids . Using a high‐throughput screening assay, we have recently identified a tripeptoid with antifungal properties against C. neoformans from a combinatorial peptoid library .…”
Section: Introductionmentioning
confidence: 99%
“…A host of studies have identified antibacterial peptoids, as summarized in a recent review by Molchanova et al ., however, there are limited reports of antifungal peptoids . Using a high‐throughput screening assay, we have recently identified a tripeptoid with antifungal properties against C. neoformans from a combinatorial peptoid library . Termed AEC5, this antifungal peptoid has no observable cytotoxicity against human lung, liver, or red blood cells at the minimum inhibitory concentration for C. neoformans and is fully stable in human serum containing active proteases for at least 48 hours .…”
Section: Introductionmentioning
confidence: 99%
“…However, a recently submitted study from our lab reports an antifungal compound AEC5 which shares many chemical characteristics with K15–13, including a tridecyl tail, charged amino side chain, and a bulky aromatic residue. 8 AEC5 underwent the same cytotoxic assay cell panel, but showed considerably lower toxicity compared to K15–13 and K15–10, with HepG2 TD 50 and erythrocytes HC 10 values of 56.2 and 68.7 μ g/mL, respectively. With an MIC against C. neoformans of 6.3 μ g/mL, this gave AEC5 SR values of roughly 9 against HepG2 cells and 11 against erythrocytes, representing a significantly better therapeutic window than any of the K15 variants tested here.…”
mentioning
confidence: 96%
“…To this end, we and others have explored the utility of combinatorial libraries, which allow for the rapid production of a multitude of unique compounds via split-and-pool synthesis. 811 …”
mentioning
confidence: 99%
“…Researchers have explored peptoids' utility as putative therapeutics . Specific targets have included development of peptoids as antimicrobial agents and as ligands to a variety of proteins, including vascular endothelial growth factor receptors, orexin receptors, and ubiquitin receptors, to name a few. In parallel, peptoids have shown promise as biocompatible metal‐chelating agents or pH sensors .…”
Section: Introductionmentioning
confidence: 99%